2022
DOI: 10.15381/rpb.v29i1.21205
|View full text |Cite
|
Sign up to set email alerts
|

Scorpions from Ceará State, Brazil: Distribution and ecological comments

Abstract: Scorpions are venomous synanthropic arachnids, in 2019 they were responsible for more than 37000 cases of envenomation in the state of Ceará, Northeastern Brazil. To update the knowledge about the scorpiofauna in Ceará, a distribution list of scorpions collected/received by municipal agents of the Health Surveillance Service was performed in 165 municipalities (89%) of Ceará (2018 – 2019) and deposited in the Dr. Thomaz Corrêa Aragão Entomology Laboratory scientific collection, including species distribution m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
1
1
0
3
Order By: Relevance
“…Our analysis revealed an upward trend in the number of scorpion accidents in SP: from the spring of 2008 to 2021, the RR increased eight times. This growth trend is corroborated by studies in other states of the Brazilian southeast [33] and northeast regions [34,35]. It is unknown how much of the increase can be attributed to improvements in the notification system, but also reveals the worrisome affinity of many scorpion species for anthropically modified environments, which consequently enhanced their contact with humans [2,36].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our analysis revealed an upward trend in the number of scorpion accidents in SP: from the spring of 2008 to 2021, the RR increased eight times. This growth trend is corroborated by studies in other states of the Brazilian southeast [33] and northeast regions [34,35]. It is unknown how much of the increase can be attributed to improvements in the notification system, but also reveals the worrisome affinity of many scorpion species for anthropically modified environments, which consequently enhanced their contact with humans [2,36].…”
Section: Discussionsupporting
confidence: 58%
“…It is unknown how much of the increase can be attributed to improvements in the notification system, but also reveals the worrisome affinity of many scorpion species for anthropically modified environments, which consequently enhanced their contact with humans [2,36]. Unplanned urban growth, indiscriminate use of natural resources, industrialization, and ecological imbalance induce the spread of some venomous species and increase the overlap between the areas used by these animals and humans [35,37]. Amado et al [36] confirmed the affinity of T. serrulatus for altered environments, as its modeled distribution was highly correlated with human population density in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Estudo recente de Braga et al 45 para o Estado do Ceará, mostra que o contato homemescorpião pode ser maior em função do crescimento populacional desordenado. Contudo, o clima e o habitat podem ser fatores importantes na distribuição dos escorpiões, considerando que habitats antropizados produzem diferentes padrões dinâmicos de distribuição 46,47 , e o ambiente urbano disponibiliza água, alimento, e não abriga predadores naturais (galinhas, seriema, macacos, lagartos, etc.…”
Section: Discussionunclassified
“…É através dessas informações que é possível entender as características e peculiaridades de cada espécie, bem como compreender sua relação com o meio ambiente (Lira et al, 2020;Marcelino et al, 2021;Martins et al, 2021a). Desta forma, para atingir esse objetivo, foi necessário recorrer a bibliografias recentes e contundentes que puderam auxiliar na identificação dos animais, sendo que essas bibliografias garantiram a precisão e acurácia dos dados (Mariano et al, 2018;Guidini et al, 2020;Lisboa et al, 2020;Oliveira et al, 2020b;Borges et al, 2021;Braga et al, 2022).…”
Section: Análise Do Materialsunclassified
“…Alguns dos estudos mais relevantes sobre escorpiões no Brasil incluem aqueles que abordam a distribuição geográfica das espécies (Lira et al, 2023), a composição da fauna em diferentes habitats (Pompermaier et al, 2020), os aspectos taxonômicos e filogenéticos das espécies (Braga et al, 2022), bem como os aspectos clínicos e epidemiológicos dos acidentes com escorpiões (Neves et al, 2022).…”
Section: Introductionunclassified